Perceived self-efficacy and self-care practices among diabetic patients in a Tertiary Hospital, Nepal - Dwa, N.; Panthee, B. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Diabetes Mellitus (DM) is a major public health problem worldwide and Nepal is not an exception. Complications of DM are in rise which results in major disabilities and poor quality of life. But evidences show that adoption of self-care practices can prevent those complications leading a healthy and quality life. Self-care practice is closely related to self-efficacy. Thus, present study aimed to assess perceived self-efficacy and self-care practices and to examine relationship between perceived self-efficacy and self-care practice of patients with Diabetes.Methods: This analytical cross-sectional study conducted in Patan Hospital among 100 patients was reviewed and approved by Institutional Review Committee. Samples were selected purposively and data was collected by face to face interview technique. Diabetes Self-Efficacy Scale and self-care practice questionnaire was used to measure self-efficacy and self-care practice, respectively.Results: Fifty nine percent and 81% of participants had moderate level of perceived self-efficacy and good self-care practice, respectively. There was significant moderate positive (r=0.62, p